Developing a model of adolescent addiction risk based on distress tolerance and emotion regulation: the mediating role of early maladaptive schemas - Eslampanah, Mohammadreza; Mahdian, Hossein; Jajarmi, Mahmoud (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The aim of this study was to predict the adolescent addiction risk based on distress tolerance and emotion regulation with the mediating role of early maladaptive schemas. Methods: The method of the present study was descriptive-correlation of structural equations. The statistical population of the study consisted of all male adolescents who were studying in the secondary schools of Qom in the first six months of the 2018-19 academic year, which numbered 2150 people. Among them, 400 people were selected by cluster sampling as the research sample. Measurement tools included Addiction Acceptance Scale Weed et al (1992), Disturbance Tolerance Questionnaire Simons & Gaher (2005), Cognitive Emotion Regulation Questionnaire Garnefski et al (2001) and early maladaptive Schema Questionnaire Young (1994). The data were analyzed using path analysis. Results: The results showed that distress tolerance indirectly and through the schemas of impaired constraints, other orientation and listening and inhibition indirectly was able to predict the risk of addiction. Also, the regulation of compromised and uncompromised emotion, both directly and indirectly, and through disrupted restraint schemes, other orientations, and alertness and inhibition, were able to predict the risk of addiction (p